Faktor-Faktor yang Berhubungan dengan Kepemilikan Jamban Keluarga di Desa Sipange Julu Kecamatan Sayur Matinggi Kabupaten Tapanuli Selatan Tahun 2013 - Aminah Arfah Pulungan; wirsal hasan; nurmaini * (Lingkungan dan Kesehatan Kerja, 2014)
ABSTRACT Sipange Julu Villages is one of villages in District Sayur Matinggi regency of Tapanuli Selatan. Sipange Julu villages have low family latrine ownership is only equal to 19,0 % of the 184 heads of families living in the village. Research conducted aimed to determine the characteristics (level of education and income levels) and the relationship between the respondents' level of knowledge, attitudes, habits of respondents and the role of health officer to the ownership family latrine in the village. Types of analytic study with a cross sectional study design. Respondents in this study is the head of the family who resides in the village of Sipange Julu totaling 63 people . Though the data obtained in using the chi square test and Fisher's exact. The results obtained that there is a relationship between the role of health officer (p= 0.040 (p< 0.05)) with the family latrine ownership and there is no relationship between the level of knowledge (p= 0.082 (p< 0.05)), attitude (p= 0.741 (p> 0.05)) and habits (p= 0.486 (p> 0.05)) of respondents with family latrine ownership. It is recommended that conducted cross-sectoral cooperation between government, health centers and other related sectors with the community to raise a family in the village latrine coverage Sipange Julu, enhance the role of health officer in raising public awareness about the importance of family latrines and sanitary latrines eligible family health, and the need further research on other factors relating to the ownership of the family latrine with a variable that has not been investigated in this study and different respondent. Keywords: Family Latrine Ownership